19 year old man with a sore throat, ear pain, and a red eye - Perez, Victor L. (Digital Journal of Ophthalmology, 2024)
19 year old male with a 1-2 weeks history of sore throat, sinus congestion, and ear pain who was told that his right eye was red. No other ocular symptoms were present. The patient was treated for sinusitis and conjunctivitis by an outside clinic and came for evaluation because his throat discomfort was not improving and he noticed an area of tenderness in his nose.